Case Report: Pediatric myeloid/lymphoid neoplasm with eosinophilia and PDGFRA rearrangement: The first case presenting as B-lymphoblastic lymphoma - Akiely, Reem; Almasri, Farah; Almasri, Nidal; Abu-Ghosh, Amal (Frontiers in Pediatrics, 2022)
According to the latest WHO classification of hematopoietic malignancies, myeloid and lymphoid neoplasms with eosinophilia and gene rearrangements include three specific rare diseases and one provisional entity. Myeloid/lymphoid neoplasms with platelet-derived growth factor receptor alpha (PDGFRA) rearrangements are the most frequent of these disorders and are usually present in adult males with a median age of the late 40s. Patients usually have chronic eosinophilic leukemia but can occasionally manifest as acute myeloid leukemia or extramedullary T- or B-lineage lymphoblastic lymphoma. We report a case of a previously healthy 2-year-old girl who presented with a right supraorbital swelling with no associated lymphadenopathy. Peripheral blood smear evaluation at initial presentation revealed microcytic hypochromic red blood cells and leukocytosis with marked eosinophilia, occasional myelocytes, and occasional blasts. Whole-body CT scans and PET scans revealed hypermetabolic potentially lymphomatous mass in the superior medial aspect of the right orbit in addition to splenomegaly but no evidence of hypermetabolic mediastinal, hilar, abdominal, or pelvic lymph nodes. Bone marrow aspirate and biopsy revealed hypercellular bone marrow with quantitatively decreased erythroid precursors and increased granulocytic precursors with 60% of the cells being eosinophilic cells in different stages of maturation. The diagnosis of myeloid neoplasm with eosinophilia and rearrangement of PDGFRA was made following confirmation by fluorescence in situ hybridization (FISH) test for FIP1L1-PDGFRA gene fusion. An incisional biopsy of the supraorbital mass revealed B-cell lymphoblastic lymphoma (B-LBL). FISH test for FIP1L1-PDGFRA gene fusion was positive in 70% of the cells studied. Thus, the final diagnosis was B-cell lymphoblastic lymphoma arising in the setting of myeloid/lymphoid neoplasm with eosinophilia and PDGFRA rearrangement. The patient was started on imatinib with concomitant therapy for B-LBL per the Children Oncology Group (COG) standard therapy for localized B-LBL and demonstrated a favorable outcome in the 2.5-year follow-up period. To our knowledge, this is the first pediatric case of myeloid/lymphoid neoplasm with PDGFRA rearrangement presenting with synchronous myeloproliferative disease and B-LBL. We present our diagnostic and management approach of this patient and review prior relevant pediatric cases of myeloid/lymphoid neoplasms with PDGFRA rearrangement.